The adventure of the illustrious scholar : papers presented to Oscar White Muscarella - Simpson, Elizabeth, 1947-; Muscarella, Oscar White (Culture and history of the ancient Near East, 2018)
The Adventure of the Illustrious Scholar: Papers Presented to Oscar White Muscarella, edited by Elizabeth Simpson, is a Festschrift celebrating the career of one of the foremost archaeologists of the ancient Near East. Oscar Muscarella is a former curator at the Metropolitan Museum of Art and a formidable scholar who has excavated at sites in Turkey, Iran, and the United States. He has published eight books and nearly 200 articles, excavation reports, and reviews on topics ranging from the arts of antiquity and the importance of connoisseurship, to the difficulties of dating and the problems of forgeries, the looting of ancient sites, and the antiquities trade. The forty-seven contributors are experts in the areas of Muscarella's interests and are major scholars in their fields. This volume constitutes an unusual, important, and timely addition to the archaeological and art historical literature.